Adaptive transmission scheme with delayed channel state information for multiuser MIMO-OFDM systems - LIU Min; ZHANG Xiao-fei; XU Da-zhuan (Tongxin Xuebao, 2008)
An adaptive transmission scheme combining orthogonal space-time block code and eigen-beamforming was proposed for multiuser MIMO-OFDM downlinks. The scheme uses delayed channel state information from receivers to maximize the throughput. An adaptive subcarrier allocation criterion and corresponding bit-loading algorithm were pre-sented. Simulation results show that the scheme can make full use of delayed channel state information to achieve much more throughput than non-adaptive schemes. A sub-optimal bit-loading algorithm was also presented,which is non-iterative and requires small computation. Simulation results demonstrate that the incurred throughput loss is negligible.